REMOVAL OF LEAD (Pb2+) IONS FROM AQUEOUS SOLUTION BY ADSORPTION USING SUGARCANE BAGASSE ACTIVATED CARBON COATED WITH MAGNETIC NANOPARTICLES - Muhammad, Abdullahi; Sati, S. Y.; Usman, A. H. (FUDMA Journal of Sciences, 2020)
An experiment to remove lead (II) ions through adsorption from its aqueous solution using Sugarcane Bagasse Activated carbon (SBAC) was carried out. As one of the ways employ to reduce the high cost of treatment of industrial effluents. Agricultural wastes could be considered as suitable material for the production of Activated Carbon due it high carbon contents, environmentally friendly and low cost of production. In this work, activated carbon was produced by chemical activation with sulphuric acid (H2SO4) of sugarcane bagasse materials. It was then coated with magnetic nanoparticle (Fe3O4) prepared by chemical precipitation of Fe2+ and Fe3+ salt from aqueous solution and tested for its efficiency as an adsorbent for the removal of Lead(II) ion from aqueous solution .The surface morphology, structural and functional groups present were investigated using scanning electron microscope (SEM) and Fourier transform infrared (FTIR) spectroscopy. Shift and disappearance of some adsorption bands in the sugarcane bagasse activated carbon coated with magnetic nanoparticles testify the formation of the composite. Optical properties were determined using UV Vis spectroscopy shows a wavelength ( of 400nm. Adsorption parameters such as effect of pH, contact time, initial concentration of Lead ion and adsorbent dosage were studied. Neutral medium was the optimum pH condition needed for the removal of lead with the percentage removal efficiency of 91%. It was found to be highly efficient at 0.4g of the dosage and at contact time of 60 minutes. This sugarcane bagasse is useful in adsorbing heavy metal in an aqueous solution